2016
DOI: 10.4103/0970-0218.170961
|View full text |Cite
|
Sign up to set email alerts
|

An adolescent with bestiality behaviour: Psychological evaluation and community health concerns

Abstract: Bestiality is a serious but less commonly reported form of animal cruelty occurring in a society. It is a punishable sexual offence in India. Bestiality has received little attention in recent psychiatric literature, and even though case reports have been published, an elaborate psychological assessment is often missing. This case report of 18 year old male presented here highlighted the importance of psychological assessment to emphasize on its implications for the further risk assessment of the person, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The psychological tests (TN-10, MMPI-201, PIE, WTC, Machover) showed a lower intellectual efficiency with a suspected start of a deeper, in fact psychotic process. We have found similar results of psychological testing, foremost in the area of lower intellectual functioning and inadequate social behaviour in an article by Satapathy and associates, which described a case of zoophilia of an eighteen year old boy who has, like out patient, lived on a farm, in a rural area, with a family with a large number of children, and who had not been diagnosed with another psychiatric comorbity alongside zoophilia [18]. Lastly, Amoo and associates have described a case of a twenty year old man affected with schizophrenia with premorbid zoophilic orientation and antisocial personality traits, who had due to the symptoms of endogenic psychotic process recurred zoophilic behaviour.…”
Section: Zoophilia and Other Psychiatric Disordersmentioning
confidence: 57%
“…The psychological tests (TN-10, MMPI-201, PIE, WTC, Machover) showed a lower intellectual efficiency with a suspected start of a deeper, in fact psychotic process. We have found similar results of psychological testing, foremost in the area of lower intellectual functioning and inadequate social behaviour in an article by Satapathy and associates, which described a case of zoophilia of an eighteen year old boy who has, like out patient, lived on a farm, in a rural area, with a family with a large number of children, and who had not been diagnosed with another psychiatric comorbity alongside zoophilia [18]. Lastly, Amoo and associates have described a case of a twenty year old man affected with schizophrenia with premorbid zoophilic orientation and antisocial personality traits, who had due to the symptoms of endogenic psychotic process recurred zoophilic behaviour.…”
Section: Zoophilia and Other Psychiatric Disordersmentioning
confidence: 57%
“…He also possessed very poor self-discipline andhas difficultly establishing emotional and sexual intimacy. (1)…”
Section: Case -1mentioning
confidence: 99%
“…Bestiality is a type of sexual offense in which animals are used as a means to fulfill sexual desire without any sort of emotional bonding (1) .It is also known as Animal Sexual Abuse (ASA) and includes the sexual molestation of animals, by fondling their genitalia, vaginal, anal, or oral penetration or oral-genital contacts (from person to animal and vice a versa); penetration with an object; and injuring or killing an animal for sexual gratification (17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kinsey et al (, ) found that individuals who have sex with animals may be more educated than the general population, with close to half of their subjects with a history of bestiality reporting that they had obtained a college degree. Case reports have variously documented the occurrence of human–animal sexual acts in individuals with autism (Chandradasa & Champika, ); alcohol use (Satapathy, Swain, Pandey, & Behera, ); depressive disorder, schizoaffective disorder, and antisocial personality disorder (Holoyda, ); and transvestism and pedophilia in the context of mania (Mendhekar & Mehta, ). Lesandric, Orlovic, Peitl, and Karlovic () wrote about a case of zoophilia in a young man who had sex with a cow in his early teens, persistent zoophilic fantasies throughout his teen years, then another episode of intercourse with a cow in his early 20s, before ultimately decompensating into psychosis.…”
Section: Clinical Considerationsmentioning
confidence: 99%